Evaluation of tropical forages managed for stockpiling purposes - Euclides, Valéria P.B.; Valle, Cacilda B. do; Silva, José M. da; Vieira, Antônio (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was conducted with the objectives of determining species of grasses adapted to stockpiling as well as establishing the best dates for deferment and utilization of the forage accumulated. Seven grass species were studied in a randomized block with split-split-plot design, in two replications. The grass species constituted the main plots, the deferring months the sub-plots and the utilization months the sub-sub-plots. Brachiaria decumbens, B. humidicola and Cynodon plectostachuys were superiors (P < 0.01) to the others, in terms of green dry matter (GDM). All three grasses, irrespective of diferring dates, showed reductions (P < 0.05) in green matter percentage (GMP), crude protein content and dry matter in vitro digestibility towards the later utilization dates. However, despite the reductions in GMP they were able to maintain over 2000 kg/ha of available GDM, at all utilization dates. The most adequate month for diferring B. humidicola was January, and for 8. decumbens and C. plectostachuys both January and February. However, if the two latters are to be used in the late dry season, they should be deferred in March.
Keywords: standing-hay; forage yield; nutritive value; Melinis minutiflora; Cynodon plectostachuys; Setaria anceps; Brachiaria decumbens; B. humidicola; B. ruziziensis; Panicum maximum.